IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU DI KABUPATEN BOYOLALI - Aris Tri Haryanto, Mulyono & (Transformasi, 2011)
Abstract   The purpose of this study is to examine and learn Teacher Certification Policy Implementation. In this study sample was chosen purposive sample. The authors chose informants executive officers and staff of teacher certification activities in Dinas Pendidikan, Pemuda dan Olahraga Kabupaten Boyolali. After a descriptive analysis, interviews, observation, and study the documentation can be concluded that: The government policy on teacher certification is an effort in order to improve the quality, capability, and welfare of teachers who are expected to have an impact on education quality improvement, implementation of the certification of teachers in Kabupaten Boyolali achieve the desired objectives with effective when supported by several factors, including: factors a positive attitude implementing policies, support of adequate resources both human resources, funds and adequate physical facilities in terms of quantity and quality, factors that accurate communication and participation of teachers as a participant certification.   Kata Kunci:     Komunikasi; Pertisipasi Sertifikasi